The effect of interpregnancy interval on obesity/overweight among women in the first trimester of pregnancy. Issue 3 (17th June 2017) - Ali, Elrazi A.; Almugabil, Abdelmageed; Salim, Ala; Rayis, Duria A.; Adam, Ishag
Abstract: Objective: To determine the effect of interpregnancy interval (IPI) on obesity/overweight among pregnant Sudanese women in early pregnancy. Methods: A cross‐sectional study was conducted at Saad Abu‐Alela Hospital, Khartoum, Sudan, from January to December 2015. Women with a singleton pregnancy and at least one previous pregnancy were enrolled in the first trimester. A questionnaire was used to collect clinical and sociodemographic data from the participants, and current body mass index (BMI) was calculated as weight in kilograms divided by the square of height in meters. Results: Among 1045 participants, 344 (32.9%), 424 (40.6%), and 277 (26.5%) women had short (<18 months), normal (18–30 months), and long IPIs (>30 months), respectively. BMI indicated 18 (1.7%), 408 (39.0%), 381 (36.5%), and 238 (22.8%) women were underweight (<18.5), normal weight (18.5–24.9), overweight (25.0–29.9), and obese (≥30.0), respectively. Age and proportion using contraceptives were increased among women with long IPI (both P< 0.001). When compared with women of normal weight, overweight women and obese women were more likely to have a long IPI (odds ratio 1.72, 95% confidence interval 1.08–2.93; and 1.71, 1.05–2.94, respectively). Conclusion: Long IPI was associated with obesity and overweight, which were prevalent among pregnant Sudanese women. Abstract : A long interpregnancy interval was associated with obesity and overweight, which were prevalent among pregnant Sudanese women.